1983
DOI: 10.1002/actp.1983.010340812
|View full text |Cite
|
Sign up to set email alerts
|

Plasticization mechanism and structure of polymers

Abstract: The situation of the general theory of plasticization is discussed. It is shown that the existing theories satisfactorily describe only particular cases, therefore exhibiting limited predicting capability. If the polymer and plasticizer compatibility is being evaluated unambiguously within the scope of the theory of polymer solutions then the plasticizer efficiency cannot be described unambiguously without allowance for the polymer system structure peculiarities. The necessity for studying "compatibility-effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 14 publications
(7 reference statements)
1
14
0
Order By: Relevance
“…(7) and (8) Fig. 7 give a very good correlation with the literature values ( T f ) 13) of these mixtures (see Fig. 8).…”
Section: *)supporting
confidence: 85%
“…(7) and (8) Fig. 7 give a very good correlation with the literature values ( T f ) 13) of these mixtures (see Fig. 8).…”
Section: *)supporting
confidence: 85%
“…Although these theories are widely accepted and used in plasticizer selection for polymers, Shtarkman and Razinskaya (1983) have emphasized the limitation of current theories on the mechanism of plasticization. Indeed, according to these authors, it is not possible to establish a plasticization mechanism because of the huge versatility of the investigated polymer and plasticizer systems; hence, instead of trusting on the above theories, it would be much more useful to consider the direct correlation between compatibility-efficiency-property of each investigated polymerplasticizer blend.…”
Section: Use Of Plasticizersmentioning
confidence: 99%
“…[8] The widely accepted mechanism for polymer plasticisation is believed to be the disruption of polymer-polymer interactions and the replacement with plasticiser-polymer interactions that increase the free volume within the polymer structure and so allows freer movement of the chains and hence an increase in flexibility. [9][10][11][12] le Roux reported that much of the structure and properties of Fischer-Tropsch waxes could be learnt from the closely related polyethylene polymer. [13] This may suggest that even though carnauba wax is a mixture of various molecules such as esters, hydrocarbons and fatty acids, the plasticisation mechanism for polymers could be transferable.…”
Section: Introductionmentioning
confidence: 99%